Comparison of stresses and displacements between steel and titanium mini-implants inserted with different angles: finite element analysis. - Magaña Lamas Ana Gabriela; Salas Orozco, Marco Felipe; Martínez Zumarán, Alan; Zavala Alonso Norma Verónica; Sánchez-Armass Cappello Oscar; Mariel Cárdenas Gylmar; González García Enrique (Revista Estomatología, 2023)
Objective: The objective of this study was to quantitatively evaluate the stresses and displacements of steel and titanium mini-implants inserted under different angles and applying a retraction force. Materials and Methods: A CAD model of the TD Orthodontics brand mini-implant, with a diameter of 1.3 mm and 8 mm length, was created. Afterwards, the characteristics of the materials to be evaluated (steel or titanium alloy) were assigned. A three-dimensional figure was created with two components that simulate the thickness and characteristics of cortical and trabecular bone (2 mm width of cortical bone and 18 mm depth of trabecular bone). The SolidWorks software was used to mesh the mini-implant and bone models and to perform the finite element analysis on the mini-implants with insertion angles of 30°, 60°, 90° and a simulated orthodontic retraction force of 2 N was applied on each of these finite element models. Results: In terms of the maximum von Mises stress in the different angles evaluated, it seems that there is no significant difference between the stainless steel mini-implants and the titanium mini-implants in the three angles evaluated. In terms of displacement, the titanium mini-implants in general suffered greater displacement in the three angles evaluated compared to the stainless steel mini-implants. Conclusion: Regardless of the angles, the difference in the generated stress and deformation in the stainless steel mini-implants and the titanium mini-implants under a retraction force of 2 N does not seem to be significant. Therefore, the insertion angle of the mini-implants seems to play a primary role in the amount of stress and deformation generated in the attachments used.